2019
DOI: 10.1108/jic-12-2018-0209
|View full text |Cite
|
Sign up to set email alerts
|

Does intellectual capital matter in performance management system-organizational performance relationship? Experience of higher education institutions in Indonesia

Abstract: Purpose The purpose of this paper is to investigate whether performance management system (PMS) has a positive effect on organizational performance. Furthermore, it also investigates whether intellectual capital (IC) mediates PMS-organizational performance relationship. Design/methodology/approach This study is designed as a quantitative research employing a partial least squares structural equation modeling (PLS-SEM). Using an online survey, data are collected from the HEIs managers under the Ministry of Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 90 publications
0
16
0
3
Order By: Relevance
“…Regarding the Egyptian context, a study by Elsharnouby and Elbanna (2018) found that relational capital and human capital had a significant positive impact on SCA in Egyptian HEIs. Moreover, Eltahir et al (2019) found that IC has a significant and positive impact on the financial and non-financial performance of HEIs in Egypt. This supports the thesis advanced by Kadir et al (2021), who proposed a conceptual framework for building the IC of leaders in Egyptian universities in order to accomplish SCA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the Egyptian context, a study by Elsharnouby and Elbanna (2018) found that relational capital and human capital had a significant positive impact on SCA in Egyptian HEIs. Moreover, Eltahir et al (2019) found that IC has a significant and positive impact on the financial and non-financial performance of HEIs in Egypt. This supports the thesis advanced by Kadir et al (2021), who proposed a conceptual framework for building the IC of leaders in Egyptian universities in order to accomplish SCA.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Elsharnouby and Elbanna (2018) found that human and relational capital have a significant positive influence on OL at Egyptian HEIs. In addition, a study by Eltahir et al (2019) found that IC had a significant and positive impact on OL in Egyptian HEIs. The impact of intellectual capital on organizational learning at Egyptian HEIs was also investigated by Rami and Maged (2018).…”
Section: Discussionmentioning
confidence: 99%
“…The performance and ranking of a university often serve as significant measures in the endeavor to transform the education system within a country (Aburizaizah, 2022;Boyadjieva, 2017;De La Poza et al, 2021;Tilak, 2016), including in Aceh, Indonesia. The excellence in performance and position of a university is consistently associated with its substantial contributions to the innovation system, economic growth, and social development of a region (Anggraini & El Pebrian, 2021;Chankseliani et al, 2021;Cricelli et al, 2018;Passaro et al, 2018;Tjahjadi et al, 2019;Wright & Horta, 2018). The contributions of universities to such development and progress can manifest in various forms, including research outputs yielding licenses, patents, and high-quality publications, fostering an elite cohort of graduates who are skilled and professionally employable, and the contributions of academic staff who provide services towards regional development (Anggraini & El Pebrian, 2021;Barra & Zotti, 2017;Forliano et al, 2021;Pugh et al, 2022;Tee, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon also applies to universities, where human resources and inherent intangible elements such as intellectual capital, knowledge, social capital, and other tacit dimensions form the backbone and frontline in achieving university performance and sustained competitive advantage. Human resource factors with various intangible elements constitute the core competencies of a university and serve as the primary inputs and sources for various Tridharma activities (teaching, research, and publication, as well as community and industry service), which are the three main missions of a university's existence (Anggraini & El Pebrian, 2021;Barra & Zotti, 2017;Martin-Sardesai & Guthrie, 2018;Ramírez & Gordillo, 2014;Tjahjadi et al, 2019;Ulum, 2019). Additionally, human resources are the main driving force behind the governance and management of higher education institutions, encouraging various efforts to improve performance continuously (Anggraini & El Pebrian, 2021;Cricelli et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation